Audit committee chair and financial reporting timeliness: A focus on financial, experiential and monitoring expertise. Issue 1 (16th October 2017) - Ghafran, Chaudhry; Yasmin, Sofia
Abstract : In this study, we examine the association of audit committee chair financial, experiential and monitoring expertise with the audit report lag period. We find that the experiential and monitoring expertise of audit committee chairs have a significant negative association with the delay in the audit report lag period, possibly resulting in more effective audit committee chairs, at least in the face of financial reporting timeliness. We also find that the audit committee composite compliance variable has a significant negative association with the audit report lag period, which suggests that a firm's compliance with audit committee regulations is also beneficial for financial reporting timeliness. These are important findings from the practice, academic and public policy perspectives.